2014
DOI: 10.14740/ijcp159w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implementing Breastfeeding Promotion Program in Neonatal Intensive Care Unit on Newborn Weight and Breastfeeding Practices

Abstract: Elmer This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our hospital has recently started to apply for accreditation as a baby-friendly hospital. This opportunity will ensure better competency for our neonatal nurses, and it will drive technical support from national and international agencies that will help in increasing the efficacy of breast bumping [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our hospital has recently started to apply for accreditation as a baby-friendly hospital. This opportunity will ensure better competency for our neonatal nurses, and it will drive technical support from national and international agencies that will help in increasing the efficacy of breast bumping [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly identified barriers on providing exclusive breastfeeding are identified i.e anxiety of inadequate production, premature delivery, serious medical concern, separation from the baby after birth, stress, and discomfort (Sakka 2014). Previous study reported that 38% of mothers stopped breastfeeding due to a lack of breast milk (Ghasemi et al 2015).…”
Section: Ngadiarti Et Almentioning
confidence: 99%
“…While adequate practice can prevent both communicable and non-communicable diseases such as diarrhoea, pneumonia, and cancer (Walters et al 2016). Breast milk nutritional composition correlates with the baby's physiological states and immune system to prevent infection and reduce risk of obesity (Tao et al 2017;Sakka 2014). Furthermore, breastfeeding also provides comfort which bridges the differences between pre and postnatal life for infants, acted as a natural contraception for mothers and reduces risk of maternal cancers of reproductive organs (Newton 2018;Sakka 2014).…”
Section: Introductionmentioning
confidence: 99%